2011
DOI: 10.1038/ng.945
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in TRPV4 cause an inherited arthropathy of hands and feet

Abstract: Familial digital arthropathy-brachydactyly (FDAB) is a dominantly inherited condition that is characterized by aggressive osteoarthropathy of the fingers and toes and consequent shortening of the middle and distal phalanges. Here we show in three unrelated families that FDAB is caused by mutations encoding p.Gly270Val, p.Arg271Pro and p.Phe273Leu substitutions in the intracellular ankyrin-repeat domain of the cation channel TRPV4. Functional testing of mutant TRPV4 in HEK-293 cells showed that the mutant prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
117
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 32 publications
2
117
0
Order By: Relevance
“…Interestingly, a recent study demonstrated that mutations in TRPV4 associated with diminished glycosylation abolished responses to environmental stimuli (such as hypotonicity) and decreased responses to GSK1016790A. 54 Such impaired posttranslational TRPV4 processing has been implicated in the development of familial digital arthropathy-brachydactyly. 54 Interestingly, the beneficial effects of TRPV4 activation during ARPKD might not be limited to the kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study demonstrated that mutations in TRPV4 associated with diminished glycosylation abolished responses to environmental stimuli (such as hypotonicity) and decreased responses to GSK1016790A. 54 Such impaired posttranslational TRPV4 processing has been implicated in the development of familial digital arthropathy-brachydactyly. 54 Interestingly, the beneficial effects of TRPV4 activation during ARPKD might not be limited to the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…54 Such impaired posttranslational TRPV4 processing has been implicated in the development of familial digital arthropathy-brachydactyly. 54 Interestingly, the beneficial effects of TRPV4 activation during ARPKD might not be limited to the kidney. A recent study identifies an antiproliferative role for TRPV4 in cholangiocytes from ARPKD rats and TRPV4 activation has a tendency to decrease liver cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Human TRPV4 mutations that alter channel function are known to disrupt normal skeletal development and joint health (14,(16)(17)(18), and similarly, targeted deletion of TRPV4 in mice leads to loss of chondrocyte osmotransduction and subsequently, severe joint degeneration (19). TRPV4-mediated Ca 2+ signaling has also been shown to enhance chondrogenic gene expression in chondroprogenitor cell lines (20), as well as increase matrix synthesis in chondrocyte-based self-assembled constructs (21).…”
mentioning
confidence: 99%
“…Even here, the literature is far from clear. While multiple skeletal-dysplasia alleles were reported to have higher activities, (gain-of-function, GOF) 4,21 , several were reported to have reduced activities (loss-of-function, LOF) 10,22 . A systematic study of 14 alleles found them to all be GOF mutations (below) 23 .…”
mentioning
confidence: 99%